PENGEMBANGAN TRADISI UJUNG MANTRA UNTUK MENGEMBANGKAN RASA BELONGINGNESS DI KALANGAN MAHASANTRI IBNU KATSIR PUTRI JEMBER - Mudafiatun Isriyah; Weni Kurnia Rahmawati; Khumairoh Ikromatul Hijjah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to develop a sense of belongingness among female Ibnu Katsir students by developing a product in the form of a module that can be used as a reference in addressing problems that exist among students. A sense of belongingness is a behavior that is lacking in Islamic boarding schools, this is a common problem that is rife among students, where the sense of belonging in a community is still lacking. A sense of belongingness is a behavior that should be developed, especially in the Islamic boarding school environment, because the main factor in the lack of a sense of belongingness among students is the difference in culture, ethnicity, or daily habits, where in the Islamic boarding school environment we are required to tolerate each other. The lack of a sense of belongingness among female Ibnu Katsir students is a problem that must be resolved, where there is a need for guidance and motivation that can awaken or develop a sense of belongingness. This study aims to develop the Ujung Mantra tradition as a method to increase a sense of belongingness among female students at the Ibnu Katsir Islamic Boarding School in Jember. Belongingness is a basic individual need to feel accepted and part of a group, which is crucial for the emotional and social well-being of students. However, challenges in Islamic boarding school life, such as new environments, busy routines, and group dynamics, often impact the sense of togetherness among students. The Ujung Mantra tradition, as a form of local wisdom, embodies values of togetherness, mutual support, and strengthening collective identity that are relevant for adaptation in the Islamic boarding school context.This research method used a qualitative approach with a research and development (R&D) design. Data were collected through observation, in-depth interviews, and focus group discussions (FGDs) with students, boarding school administrators, and community leaders familiar with the Ujung Mantra tradition. The results showed that implementing Ujung Mantra values through structured activities, such as communal prayer, traditional games, and community rituals, can increase mutual trust, cooperation, and connectedness among students. The development of this tradition also provides space for students to understand and integrate their cultural identity into Islamic boarding school life. This study concludes that the Ujung Mantra tradition can be an innovative approach to enhancing a sense of belonging among students.